ANTIFEEDANT EFFECTS OF VITEX NEGUNDO L. LEAF EXTRACTS ON THE STORED PRODUCT PEST, TRIBOLIUM CASTANEUM H. (COLEOPTERA: TENEBRIONIDAE) - Haridasan, P.; Gokuldas, M.; Ajaykumar, A. P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study aims to evaluate the nutritional and feeding deterrence indices of Tribolium castaneum adults caused by petroleum ether and methanol extracts of Vitex negundo. Methods: A modified method of flour disc bioassay was carried out to study the antifeedant activities of both the extracts on the stored product pest, T. castaneum. In this bioassay, the insects were allowed to feed on wheat flour treated with various concentrations (1.25%, 2.5% and 5%) of petroleum ether and methanol extracts of V. negundo (VPE and VME) for 24 h in ‘no choice' chambers. The effects of different concentrations of the extracts on relative growth rate and relative consumption rate of T. castaneum and the difference between the activities of two extracts were statistically analysed and compared by analysis of covariance (ANCOVA). Similarly, the comparison of the activities of VPE and VME, and their dose effects on the efficiency of conversion of ingested food and feeding deterrence indices of the insects were analysed by analysis of variance (ANOVA). Results: VPE and VME significantly affected growth, consumption and utilisation of food, and caused antifeedancy in T. castaneum. It was also found that both the extracts resulted in a slight reduction in growth rate of the insect, compared with that of the control. The reductions in relative growth rate (RGR) (P=0.37) and relative food consumption rate (RCR) (P<0.05) were more prominent for 2.5% and 5% of both the extracts. In nutritional studies, it was found that increase in the concentration (P<0.05) resulted in an increase in the efficiency of conversion of ingested food (ECI) significantly with both the extracts. The RGR, RCR and ECI of the insects were found to be similar with both the extracts. The extracts showed dose-dependent feeding deterrence index (FDI) for this insect (P<0.001). The activity was found to be similar with both the extracts (P=0.07). Conclusion: The present study reveals that both VPE and VME show significant antifeedancy in T. castaneum and thus they can effectively be used for the protection of grains from insects.